Education on the Use of Over-the-Counter Drugs as Preventive Health for Students at SMP Muhammadiyah 2 Kediri - Fendy Prasetyawan; Lisa Savitri; Yuneka Saristiana; Novyananda Salmasfattah (CV. Ulil Albab Corp, 2025)
This community service activity was conducted on September 20, 2024, to raise awareness among students about the safe and responsible use of over-the-counter (OTC) medications. The primary objective was to educate students on the types of OTC medications available, their proper use, potential side effects, and the importance of reading medication labels. The event involved 20 students, comprising 4 from Grade 8, 7 from Grade 9, and 9 from Grade 7, who actively participated in interactive discussions and Q&A sessions. The educational session was delivered using a combination of presentations, visual aids, and real-life examples to enhance comprehension. A post-activity evaluation through a quiz was conducted to assess the participants' understanding of the material. The results showed an average quiz score of 82.3%, with an accuracy rate of 87.6%, indicating a significant improvement in the students' knowledge of OTC medication use. The activity also included discussions on the importance of adopting healthy lifestyle habits as a preventive health measure, which resonated well with the students, reflecting their growing interest in maintaining overall health.